On Geraghty Contractive Mappings and an Application - S. Batul; F. Mehmood; D-e-Shehwar Sagheer; M. Sohail Ashraf; H. Aydi; Y. U. Gaba (Journal of Mathematics)
In this article, certain fixed point results for Geraghty-type contractions in the setting of Gr-Complete extended fuzzy b-metric spaces are established. An example is elaborated, and a supporting application is also established. Many known existing results are special cases of our obtained results.